A comparison of accountability models in school counseling programs - Mujiyati Mujiyati; Shinta Mayasari; Sofwan Adiputra (Universitas Negeri Padang, 2020)
The purpose of this study is to analyze the strengths and weaknesses of each accountability evaluation model, in order to make counseling programs easier for counselors to carry out. The method used was qualitative research, which focuses on meanings, definitions, characteristics, symbols and explanations of the concepts learned. The research data was collected through literature reviews and document analysis. In this study, descriptive document analysis methods were also used in data measurement. Descriptive analysis method aims to test the facts and meanings of a research systematically. This model was formed based on different initial goals in the implementation of counseling services. Moreover, Accountability Evaluation Models of School Counseling Program has each of its advantages and disadvantages. The counselor should choose part of the models which is appropriate to the situation and easy to implement in the school, in order for the implementation processes of the institution counseling program to be measured and planned in the future.